EFFECT OF RE-HEAT TREATMENT CONDITIONS ON MICROSTRUCTURAL REFURBISHMENT OF NICKEL BASED SUPERALLOY TURBINE BLADES, IN-738, AFTER LONG-TERM SERVICE - WANGYAO, Panyawat; KORATH, Thanaporn; HARNVIROJKUL, Theerapong; SAENGKIETTIYUT, Kanokwan; HOMKRAJAI, Veerasak (Journal of Metals, Materials and Minerals, 2022)
-